Pollutant diffusion in multiple-face tunnel construction: theoretical analysis and numerical validation - Zhou, Zelin; Liu, Rong; Liu, Maoyi; Wang, Kai; Zhou, Shijun; Jia, Jiayin; Zhao, Jinlai (Frontiers in Earth Science, 2023)
As the length of the tunnel continues to increase, it will be common for a single fan to undertake the ventilation of two or more tunnel faces. However, the construction of multiple faces in a single tunnel will lead to complex construction environment in the tunnel, mutual interference of ventilation, and difficult to discharge pollutants. Based on the simultaneous construction of multiple tunnel faces in a single tunnel, this study analyzed the transport law of pollutants. The diffusion laws of carbon monoxide and dust in multiple faces tunnel under different working conditions were obtained by numerical simulation. It is found that when both sides of the tunnel are ventilated at the same time, the air flow in the tunnel is spiral, vortex zone will appear near both sides of the face, and vortex and unstable airflow will appear at the intersection with the inclined shaft. The airflow in the non-equal length tunnel at both sides is more disordered than that in the equal length tunnel, and there will be a wider range of eddy currents at the intersection. The change of dust diffusion in non-equal length tunnel at both sides is not obvious, and the length of multiple faces tunnel has little effect on dust settlement and diffusion. The research results are of great significance for improving the construction environment of face and improving the working conditions of personnel.